'I think it adds value, but I don't use it': use, perceptions and attitudes of outdoor exercise equipment in an urban public park. Issue 1 (1st January 2018) - Sibson, Ruth; Scherrer, Pascal; Ryan, Maria M.
ABSTRACT: Public open spaces are important places that can contribute to public health initiatives through facilitating leisure-time physical activity. Using the findings from 400 self-completed questionnaires of park visitors, this exploratory study examined people's use, perception and attitudes of a specific type of outdoor exercise equipment (in the form of a stretch station circuit) installed in an urban public park in a suburb of Perth, Western Australia. The data highlights that the equipment is positively perceived by existing park users in that it is seen to add value to the park and is a 'good investment' by their local government authority. Users of the equipment did enjoy it and wanted more installed. However, there appears to be little perceived benefit in terms of its contribution to the physical activity levels of park users, particularly with regard to a key target group – those people who engage in little leisure-time physical activity.